2005
DOI: 10.1164/rccm.200405-623oc
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Relation between Body Mass Index and Asthma and Atopy in a Birth Cohort

Abstract: A raised body mass index is associated with asthma and atopy in women but not men. Population attributable fraction calculations estimate that 28% (95% confidence interval 7-45) of asthma developing in women after age 9 is due to overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
194
8
8

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(231 citation statements)
references
References 43 publications
21
194
8
8
Order By: Relevance
“…4 Another longitudinal study reporting on data collected between 9 and 26 years of age found that the BMI only predicted the incidence of asthma in females, and this relationship only appeared in late adolescence. 31 Neither of these studies reported data on the incidence of asthma after weight gain. The observation that important increases in fat mass emerge later in men than in women 13,31 may explain some inconsistent gender differences in the asthma-obesity association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Another longitudinal study reporting on data collected between 9 and 26 years of age found that the BMI only predicted the incidence of asthma in females, and this relationship only appeared in late adolescence. 31 Neither of these studies reported data on the incidence of asthma after weight gain. The observation that important increases in fat mass emerge later in men than in women 13,31 may explain some inconsistent gender differences in the asthma-obesity association.…”
Section: Discussionmentioning
confidence: 99%
“…31 Neither of these studies reported data on the incidence of asthma after weight gain. The observation that important increases in fat mass emerge later in men than in women 13,31 may explain some inconsistent gender differences in the asthma-obesity association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In the majority of these studies, the presence of asthma was detected by questionnaire, using self-reported symptoms or self-reported asthma to define the condition. However, there is little evidence from population studies that obesity is associated with objective markers of asthma such as airway hyperresponsiveness (AHR), [3][4][5][6][7] airway obstruction 8 or airway inflammation. 9 Asthma is defined by both episodic symptoms and variable airway obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Previous studies of the association between obesity and AHR have measured effects on sensitivity. [3][4][5][6][7] However, obesity is more likely to affect the maximal response, because obesity reduces operating lung volume 12 and breathing at low operating lung volumes is known to induce increased maximal airway narrowing in non-asthmatic subjects. 13,14 The effect of low lung volume on maximal airway narrowing in obese, non-asthmatic subjects has not been reported.…”
Section: Introductionmentioning
confidence: 99%